2014
DOI: 10.1007/s00436-014-4141-0
|View full text |Cite
|
Sign up to set email alerts
|

Propolis enhances the effectiveness of praziquantel in experimental schistosomiasis: biochemical and histopathological study

Abstract: Despite the wide current use of praziquantel (PZQ) in treatment of schistosomiasis, low cure rates have been recorded in many studies. The aim of this study was directed to evaluate the curative effect of propolis (Pps) alone or in combination with PZQ on biochemical, immunological, parasitological, and histological changes associated with experimental schistosomiasis in mice. Schistosoma mansoni-infected mice were divided into two experimental sets, each with four subgroups: (i) untreated, (ii) treated with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It has been reported that PZQ can reduce the hepatic damage induced by schistosoma eggs, which is attributed not only to its effect on decreasing the number of eggs but also to its possible anti-inflammatory properties (66). PZQ can also affect the host immune reaction during Schistosoma mansoni infection (67). However, there is little evidence of the effects of PZQ during the whole process of splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PZQ can reduce the hepatic damage induced by schistosoma eggs, which is attributed not only to its effect on decreasing the number of eggs but also to its possible anti-inflammatory properties (66). PZQ can also affect the host immune reaction during Schistosoma mansoni infection (67). However, there is little evidence of the effects of PZQ during the whole process of splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the obtained results are relevant in comparison with the essential oil from the leaves of Baccharis dracunculifolia, which is the botanical source of the Brazilian green propolis. [38] Mahmound and coworkers [26] reported that the extract of Egyptian propolis administered orally alone or in combination with PZQ in the experimental model of schistosomiasis displayed schistosomicidal activity in vivo and reduced both histological and biochemical alterations. Another in vivo study with Egyptian propolis [39] demonstrated the prophylactic and curative effects of propolis in experimentally infected mice when administered orally in a doses of 250 mg/kg/day.…”
Section: Viability Reduction Of S Mansoni Adult Worms After Exposurementioning
confidence: 99%
“…[15] There are several biological activities reported for propolis, such as anti-inflammatory, [16,17] antioxidant, [18,19] immunomodulatory, [20,21] antimicrobial, [22] antiviral, [23] antitumor, [24,25] and antiparasitic. [26][27][28] However, there are few studies with propolis as anthelmintic, especially against schistosomiasis. Thus, the aim of this work was to evaluate the in vitro schistosomicidal potential of the extract of Brazilian green propolis (Pex) by analyzing its role on the phenotypic alterations suffered by S. mansoni worms and its eggs.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that PZQ can not only kill schistosomes but also affect the host immune reaction (Mahmoud et al 2014). However, there is little evidence for the effects of PZQ during the whole process of granulomatous reaction.…”
Section: Discussionmentioning
confidence: 99%